KONTEKSTUALISASI KEADILAN DALAM HUKUM QISAS - Nur, Muhammad Tahmid (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
One of the rules of God which must be implemented is qisas. Regardless of the conflicts that occur among law experts about procedures for qisas law, there are the values of justice that should be considered and not found in any other law enforcement. It was part of the Almighty God who always wants justice for human benefit.